(untitled) (Педагогіка вищої та середньої школи, 2008)
The present article reveals the problem of organization of forming conditions of the culture of pedagogical intercourse of the future teacher. The author of the article claims that building of dialogue training situation makes for the effective forming of the culture ofpedagogical intercourse.